Application of Youtube-Based Learning Videos in Madrasah Aliyah - Sappaile, Baso Intang; Poncowati, Srikandi Dwi; Marlina, Marlina; Andika, Alek; Priyatno, Slamet Eko (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
The world of education and teaching is a part that cannot be separated from technological devices and the internet, educators utilizing this technology is very helpful for learning development. Therefore, this study aims to determine the utilization of Youtube as a video-based learning media. To find out the extent to which this video-based learning media is utilized, a survey was conducted to 50% of teachers who teach at high schools in Solok City by giving a questionnaire about the utilization of Youtube as a video-based learning media at the school. This type of research was conducted using descriptive quantitative. And the object of this research is educators and students at high schools in Solok City. And this data collection technique uses observation techniques using online questionnaires and online-based in-depth interviews. The results of this study are to find out if Youtube as a video-based learning media is very helpful for educators in developing learning. The limitation of this study is that researchers did not observe all educators in the Senior High School in Solok City in giving questionnaires for observation and interviews, therefore it is hoped that further researchers can conduct research that aims to be more effective and efficient in utilizing and developing Youtube as a video-based learning media.